Data-base as a Facilitador Element for the Treatment of Terminology Data - Xavier, Adriana Gonçalves (2006)
A report of the design and implementation of a database developed as an auxiliary tool for the treatment of the data collected for the research - Evaluation of the Relative Describers Sciences of the Information used in the Process of Alphabetical Indexation for the Biblioteca Setorial da Faculdade de Biblioteconomia e Comunicação/UFRGS. This evaluation is being developed based on the Teoría Comunicativa de la Terminología. In this theory the term is analyzed from the perspective of being a terminological lexical unit, its identification being necessary in a discourse situation, i.e., functioning. The database aims to speed up and to facilitate the work in the consolidation of the terms and the elaboration of definitions for the construction of a glossary. This will be constructed with the purpose to become a criterion appraiser of the relative describers in the area of Information Sciences. The database was developed according to a relational model that makes it possible to establish with bigger precision the relations between the constituent fields of the card for collecting the terminology data used in the research. The base is structured upon the following fields: compiler, source, term, definition, context, semantic marks and definition for the elaboration of the glossary. It points out that this tool can be used in other researches in terminology as well as for the construction of thesauri.